FÍSICA PARA TODOS: UMA ATIVIDADE DE EXTENSÃO UNIVERSITÁRIA COM OFICINAS DE ROBÓTICA - Staziaki, Daniela; Schonardie, Mateus Felzke; Frizzo, Leonardo Armando; Kürschner, Victor Noster; Toniazzo, Nelson Adelar; Rodrigues, Mauro Fonseca (Salão do Conhecimento, 2018)
Projeto Física para todos